2018
DOI: 10.1002/dep2.49
|View full text |Cite
|
Sign up to set email alerts
|

Sediment microfabric records mass sedimentation of colonial cyanobacteria and extensive syndepositional metazoan reworking in Pliocene sapropels

Abstract: The sapropel record of the eastern Mediterranean provides unique insight into the primary climatic, oceanographic, and biological drivers of organic carbon enrichment in marine sediments. The dominant source of organic matter, timing of oxygen depletion at the sea floor, and extent of metazoan reworking of these deposits remain unclear. These questions are addressed by combining microbeam imaging with bulk and molecular geochemical characterization of several Pliocene sapropels, revealing four microfacies whic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 107 publications
1
3
0
Order By: Relevance
“…By contrast, a sapropel-like scenario would amplify the more strongly reducing pathway of nitrite reduction via anammox, leading to an abundance of BHT-II and suppression of 2Me-hopanoid deposition. This is supported by the fact that 2Me-hopanoids were not detected in the sapropel samples studied here and have been reported only in very low concentrations for other sapropel events (Löhr et al, 2018). Importantly, regardless of whether anammox or heterotrophic denitrification consumes fixed nitrogen, diazotrophy-including algae-diazotroph symbioses-would still proliferate under either scenario.…”
Section: Implications For Ocean Anoxiasupporting
confidence: 76%
“…By contrast, a sapropel-like scenario would amplify the more strongly reducing pathway of nitrite reduction via anammox, leading to an abundance of BHT-II and suppression of 2Me-hopanoid deposition. This is supported by the fact that 2Me-hopanoids were not detected in the sapropel samples studied here and have been reported only in very low concentrations for other sapropel events (Löhr et al, 2018). Importantly, regardless of whether anammox or heterotrophic denitrification consumes fixed nitrogen, diazotrophy-including algae-diazotroph symbioses-would still proliferate under either scenario.…”
Section: Implications For Ocean Anoxiasupporting
confidence: 76%
“…S9). Finally, Neogene sapropel events in the subtropical Mediterranean Sea that featured conditions superficially similar to OAEs (low N/P, water column stratification, anoxia, enhanced nitrogen fixation) together with an expansion of heterocystous, nitrogen-fixing cyanobacteria (Nostocales) (72) resulted in the deposition of only trace amounts of methylhopanoids (73) relative to large amounts of nonmethylated hopanoids (74,75).…”
Section: Resultsmentioning
confidence: 99%
“…Two distinct modes of nitrogen cycling during ocean anoxia. Despite their relative abundance in OAE sediments, 2-methylhopanoids are rare in modern anoxic environments and recent anoxic events such as Pliocene-Pleistocene Mediterranean sapropels (73), which like OAEs, are associated with marine nitrogen cycle perturbations (80,81). This contrasting behavior raises questions about oceanographic influences on 2-methylhopanoid production.…”
Section: Resultsmentioning
confidence: 99%
“…Studies of modern (Wakeham et al 1993;Sinninghe Damsté et al 2003) and ancient sediments (e.g. Freeman et al 1990;Kenig et al 1995;Behrooz et al 2018;Löhr et al 2018) have shown that preservation of lycopane is highest when bottom waters are anoxic.…”
Section: C Fluctuations In Oxygen Concentration Of Bottom Waters Amentioning
confidence: 99%